Implications of Fatty Acids for Age-Related Macular Degeneration: Evidence and Recommendations - Shivantika Bisen; Nikhlesh K. Singh (Cells)
Age-related macular degeneration (AMD) is an ocular pathology in humans characterized by the buildup of lipid-rich extracellular deposits, which leads to retinal degeneration. In recent years, considerable effort has been made to observe the effect of dietary fatty acids on oxidative stress and inflammation. In continuation of this, much effort has been made to study the effect of dietary fatty acids on the pathogenesis of AMD. Although studies have shown that dietary fatty acids are effective against few forms of AMD, particularly wet AMD or neovascular AMD, no dietary lipids have shown any conclusive results for dry AMD or geographic AMD. It is therefore important to look for new lipids and lipoproteins that can be helpful in treating various stages of AMD. This article reviews the impact of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), and polyunsaturated fatty acids (PUFAs) on retinal health and the progression of AMD. Furthermore, this manuscript discusses all studies investigating the implications of fatty acids on AMD, which may be beneficial for future treatment strategies and dietary guidelines related to it. In conclusion, studies suggest that omega-3 PUFAs, particularly docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), might provide protection against AMD, highlighting the necessity for additional clinical trials to evaluate their efficacy in the prevention and treatment of AMD.